Individual predictors of vaccine hesitancy in the Italian post COVID-19 pandemic era - Carmelo M Vicario; Massimo Mucciardi; Giulia Faraone; Chiara Lucifora; Hannah M Schade; Alessandra Falzone; Mohammad A Salehinejad; Giuseppe Craparo; Michael A Nitsche (Human Vaccines & Immunotherapeutics)
A wide range of survey studies have explored vaccination hesitancy/resistance during the COVID-19 pandemic and provided evidence that this can be explained by several individual variables from the ideological, clinical, and socio-affective domain. However, evidence about which individual variables predict vaccine hesitancy in the post-pandemic state of COVID-19 is meager. We administered a battery of questionnaires to a group of 120 Italian participants with high and low scores on the adult vaccine hesitancy scale (aVHS) to investigate the predictive role of ideological (i.e. political orientation), clinical (i.e. anxiety, interoceptive accuracy), and socio-affective (i.e. alexithymia, disgust sensitivity/propensity, empathy) variables on vaccine hesitancy/resistance. This study provides evidence that lower interoceptive awareness and cognitive empathy are predictors of a greater hesitancy to get vaccinated in the post-pandemic COVID-19 state.